## #6 NEED HELP! BADLY!! What’s the solution set to – 1/6(x-18)+1/2(x+2)=x+8

Question

#6 NEED HELP! BADLY!! What’s the solution set to – 1/6(x-18)+1/2(x+2)=x+8

0

1. Hello,

Never fear papaman is here to help.

(−

1

6

)(x−18)+

1

2

(x+2)=x+8

Step 1: Simplify both sides of the equation.

(−

1

6

)(x−18)+

1

2

(x+2)=x+8

(−

1

6

)(x)+(−

1

6

)(−18)+(

1

2

)(x)+(

1

2

)(2)=x+8(Distribute)

−1

6

x+3+

1

2

x+1=x+8

(

−1

6

x+

1

2

x)+(3+1)=x+8(Combine Like Terms)

1

3

x+4=x+8

1

3

x+4=x+8

Step 2: Subtract x from both sides.

1

3

x+4−x=x+8−x

−2

3

x+4=8

Step 3: Subtract 4 from both sides.

−2

3

x+4−4=8−4

−2

3

x=4

Step 4: Multiply both sides by 3/(-2).

(

3

−2

)*(

−2

3

x)=(

3

−2

)*(4)

x=−6

x=−6

Have a nice day

~ Papa guy

2. simplify the equation to the form, which is simple to understand

-1/6(x-18)+1/2(x+2)=x+8

Simplifying:

-0.166666666667*(x-18)+1/2*(x+2)=x+8

Simplifying:

-0.166666666667*(x-18) + 0.5*(x+2)=x+8

Reorder the terms in parentheses

+(-0.166666666667x+3) + 0.5*(x+2)=x+8

Remove unnecessary parentheses

-0.166666666667x+3 + 0.5+*(+x+2+)=+x+8

Reorder the terms in parentheses

-0.166666666667x+3+( + 0.5x+1)=x+8

Remove unnecessary parentheses

-0.166666666667x+3 + 0.5x+1=+x+8

move all terms containing x to the left and all other terms to the right.

-0.166666666667x + 0.5x-1x=+8-3-1

simplify left and right side of the equation.

-0.666666666667x=+4

divide both sides of the equation by -0.666666666667 to get x.

x=-6

Hope I helped.